Keefektifan Inovasi Media Interaktif Whack A Mole dan Flip Tiles Berbasis LKPD dalam Pembelajaran Kearifan Lokal untuk Meningkatkan Kemampuan Membaca Pemahaman Pada Siswa Kelas 3 SDN Rungkut Kidul I Surabaya - Fu’ada, Aida Syafa; Istiq’faroh, Nurul; Siantoro, Ghania Maisa (Jurnal Ilmu Sosial dan Budaya Indonesia, 2026)
This study is motivated by the low reading comprehension skills of elementary school students due to the lack of interactive and contextual learning media. This study aims to determine the effectiveness of interactive media, namely Whack A Mole and Flip Tiles based on Student Worksheets (LKPD), in local wisdom-based learning to improve reading comprehension skills of third-grade students at SDN Rungkut Kidul I Surabaya. This study employed a quantitative approach with a descriptive method. The subjects consisted of 20–30 third-grade students. Data collection techniques included tests (pre-test and post-test) and questionnaires. Data were analyzed using normality tests, homogeneity tests, and N-Gain analysis. The results showed that the data were normally distributed and homogeneous with significance values greater than 0.05. The N-Gain analysis indicated that the experimental class achieved an average score of 69.46 (moderate to high category), while the control class obtained 27.80 (low category). These findings indicate that the use of Whack A Mole and Flip Tiles interactive media based on LKPD is effective in improving students’ reading comprehension skills. This, interactive learning media based on games and local wisdom can enhance students’ learning outcomes and create more engaging, meaningful, and contextual learning.